Paired surveys for patients and physiologists in echocardiography: a single-centre experience. Issue 1 (March 2019) - Roshen, Michael; John, Sophia; Ahmet, Selda; Amersey, Rajiv; Gupta, Sandy; Collins, George
Abstract : The British Society of Echocardiography (BSE) highlights the importance of patient questionnaires as part of the quality improvement process, To this end, we implemented a novel system whereby paired surveys were completed by patients and physiologists for transthoracic echocardiography scans, allowing for parallel comparison of the experiences of service providers and end users. Anonymised questionnaires were completed for each scan by the patient and physiologist for outpatient echocardiographic scans in a teaching hospital. In 26% of the responses, patient found the scans at least slightly painful, and in 24% of scans physiologists were in discomfort. The most common reason given by physiologists for technically difficult or inadequate scans was patient discomfort. In 38% of the scans at least one person (the patient or the physiologist) was in at least some discomfort. Comparative data showed that the scans reported as most painful by patients were also reported by the physiologists as difficult and uncomfortable. In summary, these results demonstrate the feasibility of implementing paired surveys. Patient information leaflets by the BSE and National Health Service (NHS) describe echocardiography as painless but the results here indicate this is not always the case.